Income Inequality and Health Across the Mediterranean: A Panel Data Analysis - Audi, Marc (Journal of Business and Economic Options, 2022)
This article aims to investigate the relationship between income inequality, represented by Theil index, and health outcomes, proxied by life expectancy, across a panel of 10 countries spanning both the northern and southern shores of the Mediterranean Sea. By employing econometric techniques on panel data covering the period from 1990 to 2021, the study seeks to provide insights into how income inequality impacts health outcomes in different regional contexts. The sample comprises countries from both the northern and southern shores of the Mediterranean, including Tunisia, Algeria, Morocco, Libya, Egypt, France, Italy, Greece, Spain, and Slovenia. By including countries from diverse socioeconomic backgrounds, the study aims to capture a broad spectrum of experiences and shed light on the nuanced relationship between income inequality and health outcomes. The results of the analysis reveal compelling insights into the relationship between income inequality and health outcomes across the Mediterranean region. In countries situated on the northern shore, the findings demonstrate a significant and positive relationship between income inequality and improvements in individual health. This suggests that, in these contexts, greater income inequality may be associated with better health outcomes, possibly due to factors such as access to healthcare services and social determinants of health. Conversely, in countries located on the southern shore of the Mediterranean, the results indicate a significant but negative relationship between income inequality and health improvements. This suggests that in these countries, higher levels of income inequality may be linked to poorer health outcomes among the population. This could be due to a variety of factors, including limited access to healthcare services, socioeconomic disparities, and environmental conditions. Overall, the findings of this study contribute to our understanding of the complex interplay between income inequality and health outcomes in the Mediterranean region. By highlighting the divergent effects observed in countries on the northern and southern shores, the study underscores the importance of considering regional variations and contextual factors when analyzing the relationship between income inequality and health. These insights have implications for policymakers and public health practitioners seeking to address health disparities and promote equitable health outcomes across the region.